ENHANCING STUDENTS’ SPEAKING SKILLS THROUGH YOUTUBE MEDIA FOR UNIVERSITY STUDENTS - Farhan Tawakkal; Nila Kencana; Elva Utami; Yosi Marita (Universitas Islam Ogan Komering Ilir Kayuagung, 2025)
This study explores the impact of YouTube as a medium to enhance speaking skills among second-semester students of the English Education Program at Prof. Dr. Hazairin SH University, Bengkulu. This research aims to investigate whether integrating YouTube videos into language learning can effectively improve students' speaking abilities, particularly in fluency, pronunciation, grammar, and vocabulary. The study used a mixed-methods design, an experimental pre-test-post-test, and qualitative methods utilizing YouTube videos as instructional media. Data were collected through tests to gain the quantitative data, and interviews, observations, and documentation supporting it in qualitative. The data was analyzed by using both quantitative and qualitative descriptive methods. The results of this study indicate that using YouTube significantly improved students' speaking skills, particularly in the areas of fluency, pronunciation, grammar, and vocabulary. The pre-test and post-test results analysis show noticeable improvements among students who used YouTube as a learning tool. Specifically, four students (20%) achieved an